2009
DOI: 10.1007/s10653-009-9261-6
|View full text |Cite
|
Sign up to set email alerts
|

Increasing polybrominated diphenyl ether (PBDE) contamination in sediment cores from the inner Clyde Estuary, UK

Abstract: The concentrations of 16 polybrominated diphenyl ether (PBDE) congeners in six short sediment cores from the Clyde Estuary were determined by gas -chromatography mass-spectrometry. Total PBDE concentrations ranged from 1 to 2645 μg/kg and the average concentration was 287 μg/kg. BDE-209 was the main congener and varied from 1 to 2337 μg/kg. Elevated total PBDE concentrations were observed close to the sediment surface in the uppermost 10 cm of four of the six sediment cores. Comparison of the down core PBDE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
1
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 19 publications
5
35
1
5
Order By: Relevance
“…The contamination levels of Σ ICES 7 PCBs were similar to those reported for the Mersey Estuary, UK (11.7 -14.4 μg/kg dw) (Vane et al, 2007), but the values for HCB and Σ 6 BDEs were lower than those reported for the Mersey Estuary and the inner Clyde Estuary (Vane et al, 2007;Vane et al, 2010). There are no environmental quality guidelines available for PCBs, BDEs and HCB in fresh water sediment.…”
Section: Contamination Levels In Sedimentsupporting
confidence: 56%
See 1 more Smart Citation
“…The contamination levels of Σ ICES 7 PCBs were similar to those reported for the Mersey Estuary, UK (11.7 -14.4 μg/kg dw) (Vane et al, 2007), but the values for HCB and Σ 6 BDEs were lower than those reported for the Mersey Estuary and the inner Clyde Estuary (Vane et al, 2007;Vane et al, 2010). There are no environmental quality guidelines available for PCBs, BDEs and HCB in fresh water sediment.…”
Section: Contamination Levels In Sedimentsupporting
confidence: 56%
“…up to 4 or 5 µg/kg dry weight for BDE 99 and BDE 47 respectively in River Viskan, Sweden 1995 (Sellström et al, 1998); 105-400 µg/kg dw for the sum of 27 PCBs (ICES 7 PCBs 1 contributed about half of that) and up to 272 µg/kg dw for the sum of 10 tri-to hexa-BDEs (including the 6 commonly monitored ones) in the Scheldt river, Belgium (Covaci et al, 2005;Vane et al, 2007). In the UK, high levels organic pollutants have been observed in the Mersey, Clyde, and Tyne estuaries (Vane et al, 2007;Vane et al, 2010;Nicolaus et al, 2015). The concentrations of PCBs in some sediment samples from the Thames estuary were recently reported to have exceeded the Ecotoxicological Assessment Criteria (EACs) derived by the Oslo and Paris Convention (OSPAR) by up to 218 fold (Nicolaus et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…While interestingly, variable temporal trends were observed in concentrations of BDE-209 and Σ 16 penta-nona-BDEs in six sediment cores collected in 2002/3 from the highly industrialized inner Clyde Estuary in Scotland, UK (Vane et al, 2010). The highly industrialized nature of the Clyde river was reflected by the fact that the upper range concentrations detected, exceed significantly those observed in this study.…”
Section: Pbdescontrasting
confidence: 43%
“…Today, the Clyde still builds military ships at Govan and Scoutstoun; however, manufacturing is now mainly linked to light when compared with heavy industry. Consequently, the river Clyde, which flows through Glasgow City, has received pollution from the onset of the Industrial Revolution (ca AD 1770) up to the present day [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…In most industrially impacted environments, petrogenic and pyrolytic PAH sources predominate, and these have different parent PAH distributions that permit sediments contaminated with crude oil and petrol to be distinguished from combustion sources, such as coal burning and vehicular combustion emissions [3,9,10]. The known history of initial production, peak production and banning of a particular group of environmentally persistent organic compounds, which have no known natural sources, such as PCBs and/or brominated flame retardants (polybrominated diphenyl ethers, PBDEs), can be used not only to trace changing industries but also to potentially provide chronological information based upon varying product formulation histories [4]. In general, multiple analyses of anthropogenic organic chemicals are required not only to build a complete picture of urban/industrial activities but also to avoid and account for the well-known complicating effects of molecular diffusion, postdepositional transformation mediated by microbes, bioturbation and variable sediment accumulation rates.…”
Section: Introductionmentioning
confidence: 99%